(3JgPjH GdCUhds - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QGaY OQLGJ GdYGQajf Edi PQhI GdYdG, hoergHW efGRd GdLGgdjf Edi CSad OQc GdTbG (B... (3hHYO agPG cJGH (B... (3MQQJ ajg WQb GdCMcGes
(3BNQgG (B:s
(3BNQgG(B: (3hGNJda aj bHhdg ef MjK Cf GdeYJQV TCfg GdgOe ddGSJOdGd (B... (3HPdc EP Odjdg ebGhe ddOdjd GdeSJOd hdG MLQ aj GdWQjb, hCeG aj GdCUd hGdaQY, hgh SDGd GdaQb, hdjcf gPG BNQ eG fPcQg aj gPG GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 227s
(3GdPQjYI Edi JUGfja GdTjYI, L (B4: 372s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs